Principal component analysis of chlorophyll content in tobacco, bean and petunia plants exposed to different tropospheric ozone concentrations = Analiza składowych głównych zawartości chlorofilu w roślinach tytoniu, fasoli i petunii eksponowanych na stanowiskach o różnych stężeniach ozonu troposferycznego - Borowiak, Klaudia; Zbierska, Janina; Budka, Anna; Kayzer, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Three plant species were assessed in this study - ozone-sensitive and -resistant tobacco, ozone-sensitive petunia and bean. Plants were exposed to ambient air conditions for several weeks in two sites differing in tropospheric ozone concentrations in the growing season of 2009. Every week chlorophyll contents were analysed.
Keywords: ozon troposferyczny; wrażliwość; odporność; chlorofil; tropospheric ozone; sensitive; resistance; chlorophyll; principal component analysis (PCA)